Stimuli-responsive platinum and ruthenium complexes for lung cancer therapy - Zhang, Cheng; Kang, Tong; Wang, Xinyi; Song, Jiaqi; Zhang, Jia; Li, Guanying (Frontiers in Pharmacology, 2022)
Lung cancer is the most common cause of cancer-related deaths worldwide. More efficient treatments are desperately needed. For decades, the success of platinum-based anticancer drugs has promoted the exploration of metal-based agents. Four ruthenium-based complexes have also entered clinical trials as candidates for anticancer metallodrugs. However, systemic toxicity, severe side effects and drug-resistance impeded their applications and efficacy. Stimuli-responsiveness of Pt- and Ru-based complexes provide a great chance to weaken the side effects and strengthen the clinical efficacy in drug design. This review provides an overview on the stimuli-responsive Pt- and Ru-based metallic anticancer drugs for lung cancer. They are categorized as endo-stimuli-responsive, exo-stimuli-responsive, and dual-stimuli-responsive prodrugs based on the nature of stimuli. We describe various representative examples of structure, response mechanisms, and potential medical applications in lung cancer. In the end, we discuss future opportunities and challenges in this field.